2015
DOI: 10.1017/s0007114514003857
|View full text |Cite
|
Sign up to set email alerts
|

High dietary intake of vitamin C suppresses age-related thymic atrophy and contributes to the maintenance of immune cells in vitamin C-deficient senescence marker protein-30 knockout mice

Abstract: Vitamin C (VC) is an essential nutrient for humans and certain other animals. It has antioxidant properties and has been reported to ameliorate oxidative damage to lipids, DNA and proteins. However, the effects of VC on immune function are poorly understood, especially the influence of long-term high-dose VC intake on the number and function of immune cells. In the present study, to evaluate the immune effects of VC, VC-deficient senescence marker protein-30 knockout (SMP30KO) mice were fed a diet containing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…In an aging mouse model with vascular endothelium damage, antioxidant therapy can alleviated the dysfunction of aging vascular endothelium cells (4). Studies have shown that long-term addition of the antioxidant vitamin C (VC), which can reduce the immune levels associated with thymic aging (5). VC may also be involved in the function of cardiovascular endothelial cells (6), which can improve endothelial dysfunction in patients with hypertension (7).…”
Section: Introductionmentioning
confidence: 99%
“…In an aging mouse model with vascular endothelium damage, antioxidant therapy can alleviated the dysfunction of aging vascular endothelium cells (4). Studies have shown that long-term addition of the antioxidant vitamin C (VC), which can reduce the immune levels associated with thymic aging (5). VC may also be involved in the function of cardiovascular endothelial cells (6), which can improve endothelial dysfunction in patients with hypertension (7).…”
Section: Introductionmentioning
confidence: 99%
“…Increased ROS observed in thymocytes often leading to apoptosis, and its inhibition has been shown to rescue thymic atrophy induced by various conditions . To study the roles of ROS during the various models of thymic atrophy, we used the ROS quencher, NAC.…”
Section: Resultsmentioning
confidence: 99%
“…One of the host‐induced factors is the generation of ROS. The involvement of ROS in thymic atrophy is well documented and the supplementation of ROS quenchers or inhibitors is successful in reducing the extent of atrophy during ageing, viral infection and tumour growth in mice. Antioxidants such as NAC and vitamin C have been successful in increasing the survival and numbers of CD4 + T cells in the periphery of HIV patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that oral supplementation of vitamin C in mice exposed to a chemotherapeutic agent was not able to prevent a decrease in total leukocytes, lymphocytes and neutrophils counts 32 . However, long-term high-dose intake of vitamin C is effective in the maintenance of immune cells 33 .…”
Section: Discussionmentioning
confidence: 99%